PENGARUH PENJUALAN KREDIT TERHADAP SALESMAN PERFORMANCE PT. SAYAP MAS UTAMA DEPO RANGKASBITUNG - Khristina Sri Prihatin (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of salesman performance when viewed from the indicator of credit sales turnover. In this study data was collected by means of observation and documentation. T test was known as the partial test, which to see how each independent variable has its own variable on its success. The purpose was to apply T test to determine the relationship of credit sales for salesman performance obtained every month. From the result of T test, each salesman obtained following significant values : Sig.0.001 for Diki, Sig.0.007 for Endang, Sig.0.001 for Riza, Sig.0.043 for Sholeh, and Sig.0.096 for Yusup. It shows that the credit sales turnover variable conducted by Yusup does not affect the value of the salesman performance, while other salesmen have significant value of less than 0.05. Credit sales made by Diki, Endang, Riza and Sholeh are involved in the value of the salesman performance.